EFL Learners’ Perceptions on the Use of English Movies in Learning Vocabulary - Rosalia, Rosalia; Purwanti, Indah Tri; Novitri, Novitri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The present study examines students' perceptions of the utilization of English movies for vocabulary acquisition. This study employed a mixed-method research design, combining both quantitative and qualitative approaches. The study included students from the English Study Program at FKIP Universitas Riau, who were in batch 2021. The researcher employed questionnaire and interview methods to gather data regarding students' perceptions of the efficacy of using English movies as a medium for vocabulary acquisition. The questionnaire consisted of 27 items, each containing 3 indications. The highest score for the indication is achieved by students' personal attitude and the acquisition of a new language, both of which are classified as very high criteria for both indicators. The study determined that the mean score of the pupil's perceptions of the use of English movies for vocabulary acquisition is 4.0, which falls under the high criteria category. Based on the interview data, the researcher discovered some reactions from the respondents to the application of English movies for vocabulary acquisition. The interview findings indicate that English movies provide students with an opportunity to encounter terms in authentic contexts. Additionally, the students assert that they make an effort to incorporate the new vocabulary they come across in English movies into their everyday conversations.